The Implementation of the Talaqi Method in Tahfidz Learning and the Strengthening of Public Speaking Skills of Grade III–V Students at MIN 3 Ponorogo - Mahmud Rifaannudin; Sanudin Sanudin; Arifin Ilham; Rafly Yarhan; Pedri Fauzi; Irfan Fadhilah (Abdimas Indonesian Journal, 2026)
This study examines the implementation of the talaqi method in Qur’anic memorization (tahfidz) learning and the strengthening of public speaking skills among third to fifth grade students at MIN 3 Ponorogo. Islamic elementary education plays a crucial role in shaping students’ religious character and communication abilities. Therefore, integrating the talaqi method with simple public speaking training provides a balanced approach that supports both spiritual development and social competence in students. This research employs a qualitative approach through observation, interviews, and documentation conducted during the community service program of KKN Tematik 38 Group 13 from the University of Darussalam Gontor. The findings indicate that the talaqi method improves students’ accuracy in Qur’anic recitation and memorization, while public speaking activities enhance their confidence and communication skills. The collaboration between university students and the madrasah also contributes to creating a more interactive and participatory learning environment.